Evaluating oral health promotion: need for quality outcome measures - Watt RG, Harnett R, Daly B, Fuller SS, Kay E, Morgan A, Munday P, Nowjack- (Blackwell Synergy, 2006)
Oral health promotion effectiveness reviews have identified the need to improve the quality of the evaluation of interventions.